An Exploratory Study Regarding the Brand-Consumer Relationship in Social Media - OTILIA-ELENA PLATON (Global Economic Observer)
In the digital era concepts such as social networks, blogs and forums have become integrated keywords in the marketing communication strategies of brands worldwide. The old ways of building an online presence, such as simple websites, have diminished most of their relevance in front of social media tools. The ease of establishing contacts with consumers made out of these new applications propitious communication channels for more and more brands, which became present on sites like Facebook, Twitter or Google Plus, where their audience already gathered in large numbers. Social media offers the opportunity of developing close relationships with consumers and helps the brands to strengthen their awareness and image. The purpose of this paper is to present the consumers` opinions towards their relationships with brands in social media. By knowing this opinions, the brand`s communication process can be optimized and adapted to the specific consumers` needs and interests.